A bibliometric analysis based on hotspots and frontier trends of positron emission tomography/computed tomography utility in bone and soft tissue sarcoma - Xiang, Feifan; Zhang, Yue; Tan, Xiaoqi; Zhang, Jintao; Li, Tengfei; Yan, Yuanzhuo; Ma, Wenzhe; Chen, Yue (Frontiers in Oncology, 2024)
Bibliometric analysis was employed to examine the articles focusing on the diagnosis and treatment of bone and soft tissue sarcomas using positron emission tomography (PET)/computed tomography (CT). Furthermore, research hotspots and emerging trends are summarized to provide beneficial references for scholars in related fields. The search was conducted on the Web of Science for publications between January 2010 and June 2023. In total, 425 relevant publications were identified. Publications have maintained a steady growth rate for the past 13 years.The clinical application of PET/CT is a research hotspot. Future research trends focus on combining PET/CT with deep learning and/or other imaging technologies, as well as new imaging agents, and integrating diagnosis and treatment. The utilization of PET/CT is increasingly essential in the assessment and management of sarcomas, necessitating extensive, collaborative, forward-looking research to validate its efficacy.